Whole genome sequencing in clinical and public health microbiology. Issue 3 (April 2015) - Kwong, J. C.; McCallum, N.; Sintchenko, V.; Howden, B. P.
Abstract : Summary: Genomics and whole genome sequencing (WGS) have the capacity to greatly enhance knowledge and understanding of infectious diseases and clinical microbiology. The growth and availability of bench-top WGS analysers has facilitated the feasibility of genomics in clinical and public health microbiology. Given current resource and infrastructure limitations, WGS is most applicable to use in public health laboratories, reference laboratories, and hospital infection control-affiliated laboratories. As WGS represents the pinnacle for strain characterisation and epidemiological analyses, it is likely to replace traditional typing methods, resistance gene detection and other sequence-based investigations (e.g., 16S rDNA PCR) in the near future. Although genomic technologies are rapidly evolving, widespread implementation in clinical and public health microbiology laboratories is limited by the need for effective semi-automated pipelines, standardised quality control and data interpretation, bioinformatics expertise, and infrastructure. Abstract : Supplemental Digital Content is available in the text